Kann ein Heim eine Wohnung sein? - (:unkn) unknown (My University, 1974)
Diskussion über Planung, Bau und Probleme des Altenheims.
Keywords: Altenheim; Altenwohnung; Altenpflegeheim; Wohnungswesen; Sozialwesen; Gesundheitswesen; Bauwesen; Architektur; Soziologie